Effect of anthropogenic pollution on the fitness of tetracycline sensitive Shigella flexneri in Thames river water. Issue 1 (February 2018) - Maruzani, Rugare; Canali, Alessandro; Serafim, Vlad; Munoz, Leonardo Pantoja; Shah, Ajit J.; Perito, Brunella; Marvasi, Massimiliano
Abstract: Urban rivers may be source of antibiotics contamination that could support spread of antibiotic resistant bacteria (ARB) to the population. It is important to understand to what extent the presence of pollutants in urban rivers influences fitness of ARB. In an exercise to estimate this contribution, microcosms were generated from Thames river (London, UK) from different locations: upstream and downstream the city center. The concentration of the polycyclic aromatic hydrocarbons (PAHs) benzo(a)pyrene, pyrene and phenantrene was found to be 128, 171 and 128 times higher in downstream sector when compared to upstream sector, respectively. Filtered microcosms for each sector were enriched with tetracycline at lethal (10 μg/mL) and sub-lethal (10 ng/mL) concentrations and the fitness of an isogenic pair of Shigella flexneri 2a YSH6000 (tet R ) and S. flexneri 2a 1363 (tet S ) was then measured. In the presence of selective pressure in upstream microcosms, the resistant strain outcompeted the sensitive one, as expected. In contrast, sensitive S. flexneri tet S was found to significantly compete with resistant S. flexneri tet R at lethal concentrations of tetracycline in downstream microcosms, where levels of PAHs were the highest. Further experiments showed that PAHs rendered the resistant S. flexneri tet R ∼20% more sensitive to tetracycline. Sensitive S. flexneri tet S strain was able to persist at lethal concentration of tetracycline in downstream microcosms, at higher concentrations of PAHs. Our findings suggest that in a polluted river sensitive S. flexneri cells may still thrive in presence of selective pressure. Fitness tests provide an additional tool to measure bioavailability.